Perencanaan dan pengembangan wilayah - Rustiadi, Ernan; Saefulhakim, Sunsun; Panuju, Dyah R. (Jakarta : Crestpent Press dan Yayasan Obor Indonesia, 2009)
Regional planning and rural development in Indonesia.
Includes bibliographical references and indexes.
Keywords: Regional planning -- Indonesia; Rural development -- Indonesia